MENUJU TERCIPTANYA SISTEM TRANSPORTASI BERKELANJUTAN DI KOTA-KOTA BESAR DI INDONESIA - Tamin, Ofyar Z. (Jurnal Transportasi, 2007)
AbstractÂ This paper describes some urban transportation problems faced by big cities in Indoniesia. Several problems related to sustainable transportation are described and alternative solutions are presented. Transport Demand Management Policy is recommended as one alternative for solving the problems.Keywords: sustainable transportation system, transport demand management.